Dynamic voting in clubs. Issue 3 (September 2015) - Roberts, Kevin
Abstract This paper examines the process and outcomes of democratic decision-making in clubs where a club is defined by its set of members whose preferences and decisions relate to the set of members in the club: the electorate is endogenous. Examples range from international organizations like the European Union and NATO to firms, workers' cooperatives and trade unions. Although the policy space is infinite, a majority voting equilibrium exists under plausible conditions and the equilibrium rule and the dynamics of clubs are characterized. Two types of club, one where a group funds some public good and the other where a given benefit is shared by the group, are analyzed in detail.